Policing domestic violence - Richards, Laura (Blackstone's practical policing, 2008)
Introduction -- Putting domestic violence into context -- An intelligence-led approach -- Effective investigation -- Risk identification, assessment, and management -- Children and domestic violence -- Honour-based violence (HBV) -- Domestic-homicide reviews -- Information-sharing -- Civil law and other protective measures